Academic performance, educational and occupational aspirations of technical secondary school students - Bakar, Ab. Rahim; Mohamed, Shamsiah (Universiti Putra Malaysia Press, 2004)
A study was conducted to assess the academic performance, educational and occupational aspirations of students from technical secondary schools. Two hundred forty-three students were involved in the study. The findings of the study showed that technical secondary school students have high educational aspiration. The majority plan to study for at least a Bachelor degree. About 76% of them plan to enroll in technical courses especially in engineering. About 60% of the students have an average general academic ability and about 50% have an average academic ability in mathematics and sciences. No significant correlations were observed between academic achievement and educational aspirations and occupational aspiration. The majority of the students were confident in obtaining a place for further education, the area of studies and the occupations they aspired for. Students were moderately knowledgeable about the field of studies and the occupations they aspire for.